2016
DOI: 10.1074/jbc.m115.711051
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage by Caspase 8 and Mitochondrial Membrane Association Activate the BH3-only Protein Bid during TRAIL-induced Apoptosis

Abstract: The BH3-only protein Bid is known as a critical mediator of the mitochondrial pathway of apoptosis following death receptor activation. However, since full-length Bid possesses potent apoptotic activity, the role of a caspase-mediated Bid cleavage is not established in vivo. In addition, due to the fact that multiple caspases cleave Bid at the same site in vitro, the identity of the Bid-cleaving caspase during death receptor signaling remains uncertain. Moreover, as Bid maintains its overall structure followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 48 publications
4
77
0
Order By: Relevance
“…7A, the combination of miR-128 with TRAIL clearly increased the cleavage of caspase-8. However, the SIRT1 plasmid or NAC inhibited caspase-8 activation in TRAIL [20]. Our results showed that miR-128 significantly enhanced the translocation of tBid to mitochondria in TRAIL-treated SW480 cells (Fig.…”
Section: Mir-128 Promotes Trail-induced Mitochondrial Apoptosis In Crcsupporting
confidence: 52%
“…7A, the combination of miR-128 with TRAIL clearly increased the cleavage of caspase-8. However, the SIRT1 plasmid or NAC inhibited caspase-8 activation in TRAIL [20]. Our results showed that miR-128 significantly enhanced the translocation of tBid to mitochondria in TRAIL-treated SW480 cells (Fig.…”
Section: Mir-128 Promotes Trail-induced Mitochondrial Apoptosis In Crcsupporting
confidence: 52%
“…Primary antibodies against DR5 (#AB16942, Milllipore), caspase-8 (#9746, Cell Signaling Technology), FLIP (#3210, Cell Signaling Technology), FADD (#610399, BD Transduction Laboratories™), CHOP (#2895, Cell Signaling Technology), β-actin (Santa Cruz Biotechnology) and Bid (kindly provided by Dr. Xu Luo) [20] were used to detect relevant proteins of interest.…”
Section: Methodsmentioning
confidence: 99%
“…37 Briefly, Calu-1 cells were seeded (1×10 5 per well) on to 12-well plates 24 h prior to exposure to 50 µg/mL AuNPs with various sizes for 3, 6, and 12 h. Cells were washed three times with phosphate-buffered saline (PBS) to remove free AuNPs. Samples were then trypsinized and suspended in medium, and the uptake amount of AuNPs was analyzed with FACScan flow cytometry (BD Biosciences).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…3,4 TRAIL binding to its receptors leads to the assembly of death-inducing signaling complex by recruiting Fas-associated death domain and caspase-8, which in turn initiates a cascade of caspase activation events mediating apoptosis. 5 Preclinical trials reported that recombinant TRAIL and its receptor agonists have been shown to preferentially eliminate cancer cells while leaving normal cells Recently, gold nanoparticles (AuNPs) have been shown to hold great promise for future applications because of their distinctive properties, such as small size, unique photophysical features, easy to surface modify, and favorable biocompatibility. 9,10 All these properties render AuNPs as a versatile nanoplatform for emerging biomedical applications in the design of biosensors, targeted drug delivery vehicles, photothermal therapy, and diagnostic bioimaging.…”
Section: Introductionmentioning
confidence: 99%